Revealing residents' shared values through crowdsourced photography - Nikšič, Matej (Urbani izziv, 2018)
Many cities in the developed world face a need for a regeneration of the aged-up urban quarters. Typical examples are the modernist urban neighbourhoods built in European cities after World War II. At the time of their construction, they represented new living standards but need to be regenerated to be able to cope with the needs and expectations of contemporary residents. These expectations largely depend on the residents' own perceptions and evaluations of the state of the art of their living environments. This paper presents an experimental approach to revealing such perceptions. The approach is based on crowdsourced analytical photography and attached descriptions. It was initially developed as a part of the EU project Human Cities to offer citizens of Ljubljana a tool to express their concerns about their living environments. It is focused on revealing shared values of local communities, which are seen as a starting point for setting up participatory urban regeneration strategies.
Keywords: fotografija; javna participacija; javni prostori; participatory urban design; photography; prebivalci; public participation; public space; residents; shared values